HBOC alleviated tumour hypoxia during radiotherapy more intensely in large solid tumours than regular ones - Yingcan Xu; Kehui Zhu; Jiakang Wu; Shifan Zheng; Rui Zhong; Wentao Zhou; Ye Cao; Jiaxin Liu; Hong Wang (Artificial Cells, Nanomedicine, and Biotechnology)
Radiotherapy (RT) is a highly valuable method in cancer therapy, but its therapeutic efficacy is limited by its side effects and tumour radiation resistance. The resistance is mainly induced by hypoxia in the tumour microenvironment (TME). As a nano-oxygen carrier, Haemoglobin-based oxygen carriers (HBOCs) administration is a promising strategy to alleviate tumour hypoxia which may remodel TME to ameliorate radiation resistance and enable RT more effective. In this study, we administered fractionated RT combined with HBOC to treat Miapaca-2 cell and Hela cell xenografts on nude mice. The study found that HBOC relieved hypoxic environment and down-regulate expression of hypoxia-inducible factor-1α (Hif-1α) both in regular (100 mm3) and large (360/400 mm3) tumours. The proliferation and metastasis of tumour tissue also decreased after HBOC application. Nevertheless, in vivo RT combined with HBOC performed more effectively to suppress tumour growth in large tumours than in regular tumours. This is due to more severe hypoxic regions exist in the large solid tumours compared to the regular counterparts, and HBOC administration may be more effective in alleviating hypoxia in large tumours. Thus, HBOC sensitization therapy is more suitable for large solid tumours.